The Construction of an Ideal Mother amid the Covid 19 Pandemic: Gender Injustice Experienced by Career Women while Working From Home - Yelly Elanda (HUMANISMA : Journal of Gender Studies, 2021)
During the COVID-19 pandemic, all activities must be carried out at home, whether working, studying, or worshiping. Working from home is currently known as WFH (Work From Home). WFH seems to be something they want and expects for workers who are still active outside the home. But what about the WFH actors themselves? The media, through their articles, have written a lot about the story of working mothers who are doing WFH. This discussion becomes intriguing when the construction of the ideal mother remains on patriarchal ideology, causing gender inequality. This paper uses a critical discourse analysis method by collecting articles about women who continue to carry out their roles as career women during the WFH period. Seventy-two articles appear in the google search engine when looking for WFH mothers during the covid 19 pandemics. However, from 72 articles, there are only 19 articles that talk about the stories of women who are doing WFH, tips and tricks on being a mother during WFH. In the article, the media constructs the ideal mother figure during the covid 19 pandemics. The ideal mother figure described by the media is a mother as a husband's servant, financial regulator, educator, child caretaker, and career woman. The construction of an ideal mother during this pandemic must carry out the four identities that are attached to her at once. The form of this identity is influenced by the ideology that coexists in society. These ideologies are patriarchal culture, ibuism, and capitalism.Masa pandemi covid 19 menyebabkan semua kegiatan harus dilakukan di dalam rumah, baik bekerja, belajar maupun beribadah. Bekerja di dalam rumah saat ini dikenal dengan istilah WFH (Work From Home). Bagi para pekerja yang masih terus beraktivitas di luar rumah, WFH seolah menjadi suatu hal yang diinginkan dan diharapkan. Namun bagaimana bagi pelaku WFH itu sendiri? Media melalui artikelnya banyak menulis tentang kisah ibu pekerja yang sedang melakukan WFH. Pembahasan ini menjadi menarik ketika ranah public dipaksa untuk dijalankan di ruang domestik. Tulisan ini menggunakan metode analisis wacana kritis dengan mengumpulkan artikel tentang ibu rumah tangga yang tetap menjalankan peran sebagai wanita karier selama masa WFH. Ada 72 artikel yang muncul dalam mesin pencari google ketika mencari ibu WFH masa pandemi covid 19. Namun dari 72 artikel hanya terdapat 19 artikel yang berbicara tentang curhatan para ibu rumah tangga yang sedang melakukan WFH, tips dan trik menjadi ibu selama WFH. Dalam artikel tersebut, media membentuk identitas mengenai sosok ibu ideal di tengah pandemi covid 19. Sosok motherhood  tersebut adalah ibu sebagai pelayan suami, pengatur keuangan, pendidik dan pengasuh anak, dan sebagai wanita karier. Seorang ibu ideal di tengah pandemi ini harus bisa menjalankan empat identitas yang telah melekat pada dirinya sekaligus. Pembentukan identitas tersebut dipengaruhi oleh ideologi yang ada pada masyarakat. Ideologi tersebut adalah budaya patriarkhi, ibuisme dan kapitalisme.